Variation characteristics of soil erosion and their response to landscape patterns in a typical basin in the Upper Yangtze River - Jiang, Kaixin; Mo, Shuhong; Zhang, Jingzhe; Yu, Kunxia; Li, Zhanbin (Frontiers in Plant Science, 2025)
Soil erosion is undeniably a significant cause of a variety of problems in the Upper Yangtze River (UYR), including floods, land degradation, and sedimentation in rivers. Recognizing alterations in soil erosion and its influencing variables in this area recently is a crucial scientific challenge requiring prompt solutions in regional soil erosion control. This study examines soil erosion and its influencing factors in the Jialing River Basin (JRB) from 1990 to 2018 using RUSLE and geographical detector. It focuses on the relationship between land use, landscape patterns, and soil erosion in this typical basin in the UYR. The results indicated that: (1) The average soil erosion modulus of the JRB decreased during 1990-2018, with predominant slight (< 500 t·km−2·a−1) and light (< 2,500 t·km−2·a−1) erosion intensity. Moderate and higher grades of erosion mainly occurred in the middle and lower JRB. (2) Cultivated land, forest land, and grassland accounted for over 97% of the JRB’s land use from 1990-2018, with cultivated land dominating the middle and lower areas. Over the years, there was an increase in forest land and construction areas, while cultivated land decreased. The landscape pattern was characterized by diversity, fragmentation, and decentralization. (3) The soil erosion control area (SECA), primarily situated in the middle and lower JRB, was predominantly cultivated land. Between 1990 and 2018, the SECA area underwent significant changes, with the most notable changes occurring in the lower Fujiang River Basin (FRB) and the western and middle parts of the Qujiang River Basin (QRB). The area experienced more fluctuations on the left bank of the JRB and the right bank of the JRB, specifically in the QRB and FRB. The research can serve as a reference for future decision-making on land use planning and soil erosion management in the UYR.